Age of Ingenuity : Re-imagining 21st Century International Cooperation. (International Monetary Fund, 2019)
International Monetary Fund Managing Director Christine Lagarde delivered this address at the Library of Congress as part of the Library's Henry A. Kissinger Lecture Series in Washington, D.C. on December 4, 2018.